AFM1 secretion and efficacy of Novasil™ clay in Kenyan dairy cows - Kuboka, Maureen; Njue, L.; Mutua, Florence K.; Grace, Delia; Lindahl, Johanna F. (MDPI, 2022)
The occurrence of aflatoxin M1 (AFM1) in milk has been widely reported in Kenya, with levels frequently exceeding national and international thresholds. Exposure to aflatoxin increases the risk of hepatic cancers and can also have other negative health impacts in children such as growth impairment and immunosuppression. Anti-mycotoxin agents (AMAs) included in contaminated feeds can greatly reduce the amount of AFM1 released in milk. A 45-day trial was designed to assess secretion of AFM1 in milk from individual cows fed commercial Kenyan dairy feed, as well as the efficacy of Novasil™ Plus in reducing the levels. A four-by-four Latin square cross-over design was used for the experiment. Four cows were fed on naturally contaminated with AFB1 feed, with levels ranging from 19 to 47 µg/kg, and either no binder or inclusion of binder at the rate of 0.6 or 1.2%. Milk samples were collected each day and analyzed for AFM1. The results showed that AFM1 levels in the milk varied between the cows, even when fed similar levels of contaminated feed. On average, inclusion of 0.6% binder into the diet resulted in 34% decline in milk AFM1 levels, while 1.2% binder dose resulted in a decline of 45%. Significant reduction in AFM1 secretion was observed in all experimental units (p < 0.005), though only minimal reduction was recorded in one of the units (Cow 4) compared to the other three. This trial shows novel data on aflatoxin exposure and excretion in Kenyan dairy cows in a field setting where AFB1 level is uncontrolled. We demonstrate significant reduction in AFM1 secretion in milk using AMA, though AFM1 levels were still above the recommended EC standard of 50 ŋg/kg. This study suggests that AMAs alone cannot be relied on to reduce AFM1 in milk to safe levels. Training and good feeding practices are recommended in addition to use of AMAs.